Design, synthesis, and characterization of a novel dual cross-linked gelatin-based bioadhesive for hard and soft tissues adhesion capability. (1st November 2022) - Pirmoradian, Maryam; Hooshmand, Tabassom; Najafi, Farhood; Haghbin Nazarpak, Masoumeh; Davaie, Sotoudeh
Abstract: Many surgical treatments require a suitable tissue adhesive that maintains its performance in wet conditions and can be applied simultaneously for hard and soft tissues. In the present study, a dual cross-linked tissue adhesive was synthesized by mixing the gelatin methacryloyl (Gel-MA) and gelatin-dopamine conjugate (Gel-Dopa). The setting reaction was based on a photopolymerization process in the presence of a combination of riboflavin and triethanolamine and a chemical cross-linking process attributed to the genipin as a natural cross-linker. Modified gelatin macromolecules were characterized and the best wavelength for free radical generation in the presence of riboflavin was obtained. Tissue adhesives were prepared with 30% hydrogels of Gel-MA and Gel-Dopa with different ratios in distilled water. The gelation occurred in a short time after light irradiation. The chemical, mechanical, physical, and cytotoxicity properties of the tissue adhesives were evaluated. The results showed that despite photopolymerization, chemical crosslinking with genipin played a more critical role in the setting process. Water uptake, degradation behavior, cytotoxicity, and adhesion properties of the adhesives were correlated with the ratio of the components. The SEM images showed a porous structure that could ensure the entry of cells and nutrients into the surgical area. While acceptable properties in most experiments were observed, all features were improved as the Gel-Dopa ratio increased. Also, the obtained hydrogels revealed excellent adhesive properties, particularly with bone even after wet incubation, and it was attributed to the amount of gelatin-dopamine conjugate. From the obtained results, it was concluded that a dual adhesive hydrogel based on gelatin macromolecules could be a good candidate as a tissue adhesive in wet condition.